2007
DOI: 10.1017/s0007485307004798
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic revision, biology and morphology of immature stages of theEntedon sparetusspecies group (Hymenoptera: Eulophidae), egg-larval endoparasitoids of weevils (Coleoptera: Curculionidae)

Abstract: The sparetus-group of Entedon is revised. Six species are recognized for the group, including one new species, E. lucasi Gumovsky sp. n., which is described from Algeria. All species are either diagnosed or described, and illustrated, and new distribution records are provided. An illustrated dichotomous key to all species of the group is given. Biology of two species, E. thomsonianus Erdös and E. sparetus Walker, is studied in detail: both species proved to be egg-larval parasitoids of stem-boring weevils, Lix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…Parasites of Gymnetron are few (May 1993, Gumovsky 2007), and during this study, only one parasite was found in the larvae of Gymnetron . Low parasitism may due to the following two reasons.…”
Section: Discussionmentioning
confidence: 55%
“…Parasites of Gymnetron are few (May 1993, Gumovsky 2007), and during this study, only one parasite was found in the larvae of Gymnetron . Low parasitism may due to the following two reasons.…”
Section: Discussionmentioning
confidence: 55%
“…7b, d). Shortly afterwards the ovipositor's needle appears within the egg yolk, the female carries out rhythmic, twisting movements of her gaster, similarly to other species of the genus (Gumovsky, 2007(Gumovsky, , 2008. Oviposition lasts 1-3 min or longer.…”
Section: The Parasitoid Entedon Erythrinaementioning
confidence: 99%
“…The other known gregarious parasitoids of Entedon (the cioni group) attack the larvae of their hosts, Cionus weevils (Curculionidae) (Gumovsky, 1997). The other known egg-larval species of genus are all solitary parasitoids (Gumovsky, 2007(Gumovsky, , 2008. Entedon erythrinae is proovigenic species.…”
Section: Parasitoid Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphological characterizations of immature stages aiding in taxonomy (Gumovsky 2007). However, for this species does not well elucidated.…”
Section: Introductionmentioning
confidence: 97%